2020
DOI: 10.18502/kss.v4i3.6371
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Service Quality and Corporate Image Against Satisfaction and Customer Loyalty

Abstract: The purpose of the study looked at the influence: (1) Perceptions of service quality and corporate image directly on customer satisfaction; (2) Perceptions of service quality, corporate image, and satisfaction directly on customer loyalty; (3) Perceptions service quality and corporate image indirectly on loyalty through customer satisfaction at Travel Prima. The type of research data used comes from the primary (interview questionnaire to the respondent) and secondary (scientific books, articles, or internet).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The study utilized the Stimulus-Organism-Response (SOR) model and the results revealed that there is a significant effect between service quality, corporate image, student satisfaction, and student loyalty in the HEIs context. This has also yielded the similar outcomes with numerous past studies that examined service quality of the various services industry (Ashraf et al, 2018), such as travel companies (Maria et al, 2020), restaurants (Martey et al, 2018), supermarkets (Dam & Dam, 2021).…”
Section: Relationship Between Service Quality and Various Outcome Var...supporting
confidence: 74%
“…The study utilized the Stimulus-Organism-Response (SOR) model and the results revealed that there is a significant effect between service quality, corporate image, student satisfaction, and student loyalty in the HEIs context. This has also yielded the similar outcomes with numerous past studies that examined service quality of the various services industry (Ashraf et al, 2018), such as travel companies (Maria et al, 2020), restaurants (Martey et al, 2018), supermarkets (Dam & Dam, 2021).…”
Section: Relationship Between Service Quality and Various Outcome Var...supporting
confidence: 74%
“…Second is operational leadership, to prepare management skills to overcome the turmoil of change. The meaning is to identify and provide managers at the operational level with operational leadership and vision like never before (Pearce & Robinson, 2010;Maria et al, 2020;Faradila et al, 2020). Bartlett & Ghoshal (2001) Several studies conducted by Bartlett & Ghoshal (1997) on the most successful global companies in the last ten years concluded that combining the ability to respond flexibly to integration and innovation requires rethinking the management role and distribution of management roles mature companies (Maria et al, 2019).…”
Section: Strategic Leadership and Operational Leadershipmentioning
confidence: 99%
“…The form of service in question is all objective physical factors controlled by the company to bind and limit the actions of employees and customers. How important this explanation is, that the store atmosphere can affect SERVQUAL (Baker et al 1992;Bitner, 1992;Prashar et al, 2015;Maria et al, 2020).…”
Section: Store Atmospherementioning
confidence: 99%
“…This is because SERVQUAL is the main instrument that will make customers behave positively to be able to recommend and promote company products to others. Thus, increasing SERVQUAL will have a positive impact on customer satisfaction (Ho, Lee, 2007;Bendall-Lyon & Powers, 2004;Gounaris et al, 2003;Desiyanti et al, 2018;Maria et al, 2020).…”
Section: Servqualmentioning
confidence: 99%